2009
DOI: 10.53841/bpsfpop.2009.1.107.41
|View full text |Cite
|
Sign up to set email alerts
|

How do you evaluate an informal support group? A pilot example from stroke rehabilitation

Abstract: In order to justify the use of limited resources there is an increasing demand to evaluate the effectiveness of interventions within the health service. Despite this, the literature indicates that designing and implementing effective evaluations is difficult and often poorly done. Further, clinicians’ negative perceptions of research may discourage evaluation, resulting in practice that is primarily based on clinical intuition. The current article describes the rationale behind the development of a pilot evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous work has piloted an activities based in-patient support group in a stroke rehabilitation setting and found that it was viewed positively by participants (Hull, Hartigan & Kneebone, 2007). A later evaluation identified broad benefits including stimulation, social networking and "time out" from rehabilitation (Dewar, Jenkins & Kneebone, 2009). Similar work piloting a peer support group within a younger stroke population also found benefits such as improved socialization (Muller Toth-Cohen & Mulcahey, 2014).…”
mentioning
confidence: 96%
“…Previous work has piloted an activities based in-patient support group in a stroke rehabilitation setting and found that it was viewed positively by participants (Hull, Hartigan & Kneebone, 2007). A later evaluation identified broad benefits including stimulation, social networking and "time out" from rehabilitation (Dewar, Jenkins & Kneebone, 2009). Similar work piloting a peer support group within a younger stroke population also found benefits such as improved socialization (Muller Toth-Cohen & Mulcahey, 2014).…”
mentioning
confidence: 96%